Today’s diverse nano-theranostic applications and tomorrow’s promises - Webster TJ (Dove Medical Press, 2015)
Thomas J Webster,1 Sanwha Lee,2 Seong Soo A An3 1Department of Chemical Engineering, Northeastern University, Boston, MA, USA; 2Department of Chemical and Biochemical Engineering, Gachon University, Sungnamsi, Gyeonggido, South Korea; 3Department of BionanoTechnology, Gachon Medical Research Institute, Gachon University, Sungnamsi, Gyeonggido, South KoreaIn 2004, the US Food and Drug Administration (FDA) released an important report entitled Innovation/Stagnation: Challenges and Opportunities on the Critical Path to New Medical Products.1 In this report, the FDA strongly expressed its interest in modernizing manufacturing processes (or scientific tools) for medical products. Theranostics was indicated as one of the best candidates that can epochally change such scientific tools toward a critical path to new medical products. Since the concept was first introduced in 1998 by John Finkhouser, theranostics has been generally considered as combining therapy and diagnosis into one approach in order to develop an efficient new targeted therapy for personalized medicine. Theranostics was a term created by combining the two words, therapy and diagnostics, into one to better present the early detection of various diseases and their respective personalized treatments. The following phrase also seems to reflect the core of theranostics – have your cake and eat it too – combining these two excellent ideas of nanotechnology and theranostics into inspiration for innovative creativities. Here, nano-theranostics extends further into the convergence with nanotechnology and personalized medicine, where many researchers and scientists have been developing cutting-edge nanotechnologies and applying them into tailored medicines for each  individual. A concerted effort has been intensively invested to develop theranostic nanomaterials that can effectively combine therapeutic agents, targeting moieties, and imaging agents. For practical and clinical applications of nano-theranostics, all three components need to be cunningly integrated into nanoparticle-based carriers because of the three components feasible tailorability and functional diversity.